Lacking catalase, a protistan parasite draws on its photosynthetic ancestry to complete an antioxidant repertoire with ascorbate peroxidase - Schott, Eric (2019)
Background: Antioxidative enzymes contribute to a parasite's ability to counteract the host's intracellular killing mechanisms. The facultative intracellular oyster parasite, Perkinsus marinus, a sister taxon to dinoflagellates and apicomplexans, is responsible for mortalities of oysters along the Atlantic coast of North America. Parasite trophozoites enter molluscan hemocytes by subverting the phagocytic response while inhibiting the typical respiratory burst. Because P. marinus lacks catalase, the mechanism(s) by which the parasite evade the toxic effects of hydrogen peroxide had remained unclear. We previously found that P. marinus displays an ascorbate-dependent peroxidase (APX) activity typical of photosynthetic eukaryotes. Like other alveolates, the evolutionary history of P. marinus includes multiple endosymbiotic events. The discovery of APX in P. marinus raised the questions: From which ancestral lineage is this APX derived, and what role does it play in the parasite's life history? Results: Purification of P. marinus cytosolic APX activity identified a 32 kDa protein. Amplification of parasite cDNA with oligonucleotides corresponding to peptides of the purified protein revealed two putative APX-encoding genes, designated PmAPX1 and PmAPX2. The predicted proteins are 93% identical, and PmAPX2 carries a 30 amino acid N-terminal extension relative to PmAPX1. The P. marinus APX proteins are similar to predicted APX proteins of dinoflagellates, and they more closely resemble chloroplastic than cytosolic APX enzymes of plants. Immunofluorescence for PmAPX1 and PmAPX2 shows that PmAPX1 is cytoplasmic, while PmAPX2 is localized to the periphery of the central vacuole. Three-dimensional modeling of the predicted proteins shows pronounced differences in surface charge of PmAPX1 and PmAPX2 in the vicinity of the aperture that provides access to the heme and active site. Conclusions: PmAPX1 and PmAPX2 phylogenetic analysis suggests that they are derived from a plant ancestor. Plant ancestry is further supported by the presence of ascorbate synthesis genes in the P. marinus genome that are similar to those in plants. The localizations and 3D structures of the two APX isoforms suggest that APX fulfills multiple functions in P. marinus within two compartments. The possible role of APX in free-living and parasitic stages of the life history of P. marinus is discussed.